2021
DOI: 10.3892/ol.2021.12843
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with lentiviral vectors encoding shRNA against interleukin 10 modulates the immunosuppressive activity of murine colon carcinoma‑associated myeloid‑derived suppressor cells

Abstract: Myeloid-derived suppressor cells (MDSCs) are potent suppressors of antitumor immunity and their accumulation is often associated with poor prognosis. The aim of the present study was to determine the mechanisms of action of lentiviral vectors encoding short hairpin (sh)RNA against interleukin-10 (IL-10), with particular emphasis on their influence on the activity of tumor-derived MDSCs. Lentiviral vectors encoding shRNA against IL-10 (shIL-10 LVs) were utilized to silence the expression of IL-10 either in MDSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…This can be achieved by local or systemic blockade of IL-10 activity, e.g. by administration of shRNA against IL-10 and antibodies neutralizing IL-10 or IL-10 receptor ( 19 24 ). The temporary blockade of the IL-10-specific receptor (IL-10R) with anti-IL-10R antibodies reduces the sensitivity of immune cells to IL-10, which prevents the transformation of effector cells into suppressor cells and prepares optimal conditions for triggering an efficient anticancer response.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by local or systemic blockade of IL-10 activity, e.g. by administration of shRNA against IL-10 and antibodies neutralizing IL-10 or IL-10 receptor ( 19 24 ). The temporary blockade of the IL-10-specific receptor (IL-10R) with anti-IL-10R antibodies reduces the sensitivity of immune cells to IL-10, which prevents the transformation of effector cells into suppressor cells and prepares optimal conditions for triggering an efficient anticancer response.…”
Section: Introductionmentioning
confidence: 99%
“…To find a more effective treatment strategy for sciatic nerve injury, our study confirmed the protective effect of GDF11 on neurons in vitro , and in a further study, we used a lentiviral vector to induce GDF11 overexpression and thus create and maintain a local microenvironment conducive to nerve regeneration. Lentivirus is a safe in vivo expression vector that is currently widely used ( Anger-Gora et al, 2021 ; Reyne et al, 2021 ). Specifically, we found that lentivirus can transfer the GDF11 gene into the peripheral nervous system and overexpress GDF11 to continuously produce a large amount of GDF11 locally and thus promote the recovery of nerve function after peripheral nerve transection.…”
Section: Introductionmentioning
confidence: 99%